Maritime Cabotage Law - Akpan, Aniekan; Taylor and Francis (Boca Raton, FL : Routledge, 2018)
This is the most comprehensive review of maritime cabotage law. It introduces the new theory of Developmental Sovereignty to jurisprudence. The maritime cabotage law provisions and approaches as adopted in many states and jurisdictions has been extensively scrutinised. This book challenges the established and accepted wisdom surrounding maritime cabotage by presenting new reasoning on the underpinning principles of the concept of maritime cabotage law. The book offers a vibrant discussion on the adjustment in the regulatory approaches of maritime cabotage, from one that was intrinsically premised on the idea of national sovereignty, to one that now embraces the broader ideology of development. It investigates what the common understanding of the law of maritime cabotage should be and on what intellectual basis it can be justified. It reduces the inconsistencies and confusion that surround the concept and application of maritime cabotage law, to provide a more certain and more robust concept of maritime cabotage.
Table of contents Chapter One 1 Introduction to the Law of Maritime Cabotage 1.1 Definition and scope of maritime cabotage 1.2 Distinguishing between maritime cabotage and maritime delimitation 1.3 Historical review of maritime cabotage from fourteenth to twenty first century 1.4 Introducing the theory of Developmental Sovereignty 1.5 Overview of the fundamental themes of maritime cabotage law Chapter Two 2 The Evolutionary Synthesis in the Development of Maritime Cabotage Law and Public International Law 2.1 International Law 2.2 A comparative overview of the evolution of maritime cabotage law and public international law from seventeenth to twenty first century 2.3 The legal habitat of maritime cabotage law and public international law 2.4 The intersection of internationality and national maritime frontiers 2.5 The role of globalization in the development of maritime cabotage law Chapter Three 3 The theory of Developmental Sovereignty 3.1 The national framework of development 3.2 Applying the theory of Developmental Sovereignty to the protectionist, liberal, and flexible approaches of maritime cabotage law 3.3 The role of national and regional governments Chapter Four 4 Theories of Development and Maritime Cabotage 4.1 The linear stages of development theory 4.2 The structural change development theory 4.2.1 The Lewis model 4.2.2 The Chenery model 4.3 The international dependence revolution theory of development 4.3.1 The neo-colonial dependence model 4.3.2 The false-paradigm model 4.4 The neoclassical counterrevolution theory of development 4.4.1 The free market approach 4.4.2 The public choice approach 4.4.3 The market friendly approach Chapter Five 5 The Concepts of Economic Development and Competition Law 5.1 A review of the interface between the concepts of economic development and competition law within the context of maritime cabotage law 5.2 State aid in maritime cabotage law context 5.3 Government regulation, influence, and intervention Chapter Six 6 The Variants of Maritime Cabotage 6.1 Island cabotage 6.2 Mainland Cabotage 6.3 General Maritime Cabotage Chapter Seven 7 The Theoretical Framework of Maritime Cabotage 7.1 The international law theory on maritime cabotage law 7.2 Re-visiting the doctrines of mare liberum, mare clausum and de dominio maris 7.3 The international institutions perspective 7.3.1 World Trade Organization (WTO) dimension 7.3.2 Organization of Economic Cooperation Development (OECD) dimension Chapter Eight 8 The regulatory approaches of maritime cabotage 8.1 The Protectionist, liberal, and flexible maritime cabotage approaches 8.2 Outline of the maritime cabotage regimes of various countries Chapter Nine 9 The Protectionist Maritime Cabotage Approach 9.1 The United States of America: Section 27 of Merchant Marine Act 1920 (Jones Act) 9.1.1 Judicial Decisions Arising from the merchant marine Act of 1920 (The Jones Act) 9.1.2 United States v. 250 Kegs of Nails 9.1.3 Marine Carrier Corp. v. Fowler 9.1.4 Shipbuilders Council of America, et al. v United States of America, et al. 9.1.5 American Maritime association v. Blumenthal 9.1.6 Recent Rulings of United States Customs and Border Protection 9.1.7 Analysing the merchant marine act 1920 9.2 Canada : Coasting Trade Act 1992, Canadian Shipping Act, Part X, 1936 9.2.1 Judicial decisions arising from Canadian cabotage law 9.2.2 The RV Northern Access 9.2.3 Concluding Analysis of the Canadian Maritime Cabotage Law and Policy 9.3 Nigeria: Coastal and Inland Shipping (Cabotage) Act No. 5 of 2003 9.3.1 Judicial Decisions from The Nigerian Cabotage Law 11.3.2 ISAN and Pokat V MBX 9.3.3 Noble Drilling v NIMASA and Minister of Transport 9.3.4 Polmaz Limited v Nigerian National Petroleum Corporation 9.3.5 Analysis on Nigerian Maritime Cabotage Law 9.4 Indonesia: Maritime Law No.17 of 2008 9.5 Japan: Ship Law No. 46 of 1899 9.6 The Peoples Republic of China: Maritime Code of the Peoples Republic of China 1992 9.7 Federative Republic of Brazil: Federal Law 9432/97 9.8 The Philippines: Tariff and Customs Code of the Philippines (RA 1937) and Domestic Shipping Development Act of 2004 (RA 9295) 9.8.1 The Republic of the Philippines v The Peoples Republic of China Index Chapter Ten 10 The Liberal Maritime Cabotage Approach 10.1 The European Union: Council Regulation (EEC) NO 3577/92 10.2 Judicial Decisions Arising From Council Regulation 3577/92 10.2.1 Alpina and Nicko Tours v Chioggia Port Authority 10.2.2 Commission of the European Communities v France 10.2.3 Commission of the European Communities v Greece 10.2.4 Agip Petroli SPA v Capitaneria di Porto di Siracusa et seq 10.2.5 Commission of the European Communities v Hellenic Republic 10.2.6 Commission of the European Communities v Kingdom of Spain 10.3 The United Kingdom and the Effect of Brexit 10.4 South Africa: South African Maritime Transport Policy of 2008 10.5 New Zealand: Maritime Transport Act 1994 Chapter Eleven 11 The Flexible Maritime Cabotage Approach 11.1 The Russian Federation: The Merchant Shipping Code of 1999 11.2 The Republic of India: Section 407(1) of the Merchant Shipping Act 1958 11.3 The Federation of Malaysia: Merchant Shipping Ordinance of 1952 11.4 Australia: Coastal Trading (Revitalising Australian Shipping) Act 2012 11.5 Judicial Decisions Arising from Australian Maritime Cabotage Law 11.5.1 Re The Maritime Union of Australia & Ors; Ex parte CSL Pacific Shipping Inc 11.5.2 CSL Australia Pty Ltd v Minister for Infrastructure & Transport and Rio Tinto Pty Ltd 11.5.3 CSL Australia Pty Ltd V Minister for Infrastructure & Transport and Braemar Seascope Pty Ltd 11.5.4 Analysis of Australias New Maritime Cabotage Regime 11.6 Republic of Chile: Decreto Ley 2222 of 1978 and Decreto Ley 3059 of 1979 11.7 Maritime Cabotage Law in Sui Generis Regions 11.7.1 Maritime Cabotage in the Arctic Region Chapter Twelve 12 The Features of Maritime Cabotage 12.1 The Building and Repairing of Vessels Requirement 12.2 The Ship Registration Feature in the Country 12.3 The Ownership Requirement 12.3.1 The Shipowner in the Context of Maritime Cabotage Law 12.4 The Crew Feature Requirement 12.5 Future Features of the Law of Maritime Cabotage 12.5.1 The Ship Classification Society Requirement 12.5.2 The Ship Recycling Requirement Chapter Thirteen 13 Future Directions of Maritime Cabotage Law 13.1 A Harmonized International Maritime Cabotage Concept 13.1.1 International Agenda Based on a Mega-Regional Maritime Cabotage Regime 13.1.2 International Maritime Cabotage Relay Index.
Includes bibliographical references and index.
Also available in print format.
Keywords: LAW / Commercial / General; LAW / Commercial / International Trade; Base line; Chenery model; Coastal water; Contiguous zone; Continental shelf; chemical pollution; Developmental Sovereignty; development theory; de dominio maris; Exclusive Economic Zone (EEZ).; economic development; Gas; General cabotage; Government regulation; globalization; government; High Sea; Indigeneity; Island cabotage; internationality; legal regimes; liberal; Mainland cabotage; Maritime pollution; mare clausum; mare liberum; maritime cabotage; maritime delimitation; Nationality; national maritime frontiers; Oil; Public service contracts; Public service obligation; piracy; protectionist; public international law; Sovereignty; Sovereign rights; State aid; Territorial water; Cabotage; Maritime law; Jurisdiction; Electronic books